Masculinities and families in transformation - Genest Dufault, Sacha; Castelain Meunier, Christine (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2017)
Research Framework : The family is an important setting for gendered socialization including the way individuals are built and gendered in a normative social and cultural setting. The family contributes to the reproduction of masculinities, though it can also constitute a space for emancipation and subversion of gender norms. Objectives : This article is an introduction to the Enfances Familles Générations Journal issue on masculinity and families. It aims to present the state of research and paths of reflection on the articulation of masculinity and the family. Methodology : This introductory article is based on research into masculinity and the practices of men. The analysis is then put into context using the field of study on families and its current transformations. Results : Studies on families and men are politicized fields of research which are intimately connected. Despite recognition that transformations are currently taking place, there remains a desire for further knowledge on whether the subject of masculinity within the family is being reinvented, or whether it is still participating in the reproduction of gendered social orders. This is a complex issue which will be further explored in this text. Conclusions : Several masculinity related themes are explored in the research. The contributions made by this issue will help fill in these shortcomings. The topics we address here discuss the new realities of men in the family, including househusbsands, fathers of premature children and the evolution of social discourse on maleness. Contribution : This article reviews issues surrounding the transformation of masculinity and family plurality and identifies new paths of research to be further fleshed out regarding these issues.